Removal Of Pb And As By Bacteria Isolated From Sediments Of Las Vírgenes Dam And Río Conchos In The State Of Chihuahua, Mexico - Soto, Marisela (2022)
Lead (Pb) and Arsenic (As) are elements that negatively affect all living organisms if present in the environment. These elements have been reported in the sediments of water supply basins in the State of Chihuahua, Mexico. The current study consisted of the isolation of bacteria and investigating their growth capacity and the potential removal of Pb and As. Thus, two Gram-positive bacteria resistant to Pb and two Gram-positive bacteria resistant to As were isolated. The phylogenetic analysis -based on the 16S rRNA gene- identified them as Paenibacillus illinoisensis (Pb114002), Bacillus luti (Pb214001), Paenibacillus ginsengagri (As115004), and Bacillus freudenreichii (As215002). Paenibacillus illinoisensis (Pb114002) showed a Pb removal percentage of 65.67% in the supernatant and Bacillus luti (Pb214001) displayed 6.57%. Regarding As, removal percentages in the supernatant shown were 11.96% by Paenibacillus ginsengagri (As115004) and 42.72% by Bacillus freudenreichii (As215002).